Potential Drug–Drug Interactions Among Hospitalised Elderly Patients in Northern Sri Lanka, A Lower Middle‑Income Country: A Retrospective Analysis - Thiyahiny, S.N.; Kumanan, T.; Suthasini, S.; Sreeharan, N. (Springer Nature, 2022)
Background and Objectives Elderly individuals are more vulnerable to potential drug–drug interactions (pDDIs) as agerelated physiological changes, polypharmacy and hospitalisations are known to increase the risk of pDDIs. The aims of this study were to assess the impact of hospitalisation and other associated factors on pDDIs in elderly patients, in a resourcelimited setting. Methods This is a retrospective analysis of data of elderly patients (aged ≥ 65 years) admitted to the medical units of Jafna Teaching Hospital. Preadmission and post-admission data were collected from clinic and hospital records, respectively. The British National Formulary was used to identify and categorise pDDIs. Point prevalence of pDDIs in elderly patients and the total number of pDDIs before and after hospitalisation were estimated. Factors contributing to pDDIs were determined by univariate and multivariable logistic regression. Results Two hundred and eighty-eight hospitalised elderly patients with a median age of 71 years (interquartile range 67–76 years) showed a signifcant increase in the prevalence of pDDIs post-admission compared with the preadmission values (77.1% vs 61.5%; p < 0.001) associated with an increase in total pDDIs (377 vs 488; p < 0.001) where the majority (> 75%) were potential pharmacodynamic interactions. An unadjusted analysis showed a signifcant association between pDDI and polypharmacy [taking fve or more medications] (odds ratio [OR] = 14.17; 95% confdence interval [CI] 7.41–27.10), the presence of more than three underlying medical conditions (OR 4.14; 95% CI 1.70–10.06), ischaemic heart disease (OR 3.25; 95% CI 1.78–5.94) and asthma (OR 8.14; 95% CI 2.46–26.88). However, when adjusted for confounders only polypharmacy (OR 14.10; 95% CI 6.50–30.60) and the presence of underlying asthma (OR 11.61; 95% CI 2.82–47.85) were associated with pDDIs. Conclusions The prevalence of pDDIs among elderly patients was high and increased with hospital admissions. Polypharmacy and relevant comorbidities were contributory factors. Increased awareness of the potential for pDDIs through appropriate training and simple measures including a proper drug history, creating a bespoke pDDI list and frequent medication reviews by healthcare professionals would help to mitigate pDDIs in resource-limited and technology-limited settings.
Keywords: Potential Drug–Drug Interactions; Elderly Patients; Northern; Sri Lanka